External load training does not alter balance performance in well-trained women. Issue 3 (3rd July 2018) - Simpson, Jeffrey D.; Miller, Brandon L.; O'Neal, Eric K.; Chander, Harish; Knight, Adam C.
Abstract: This study investigated the influence of external load training (ELT) on static and dynamic balance. Nineteen females stratified into two groups (ELT = 9, control = 10) completed three testing sessions over 6 weeks. The ELT group wore weighted vests (WV) of 8% body mass for 32 h/week during daily living and three training sessions/week for 3 weeks. Following completion of ELT, a 3 week detraining (DET) phase was completed. Bilateral and unilateral static balance were assessed with eyes open and closed. Dynamic balance was assessed using the star excursion balance test (SEBT). Static and dynamic balance variables were analysed using a 2 (group) x 3 (time) between participants repeated measures ANOVA ( p < 0.05). Results revealed significant reductions in average centre of pressure (COP) velocity in the control group on the non-dominant limb with eyes closed, and significantly greater reach distances in the ELT group on the SEBT for the posteromedial and medial directions on the dominant limb ( p < 0.05). These findings suggest the ELT group did not significantly improve their balance in comparison to the control group. However, future research should further examine this unique, supplemental training method and the impact on balance performance.